2017
DOI: 10.1021/jacs.7b05803
|View full text |Cite
|
Sign up to set email alerts
|

The Transition-State Structure for Human MAT2A from Isotope Effects

Abstract: Human methionine S-adenosyltransferase (MAT2A) catalyzes the formation of S-adenosylmethionine (SAM) from ATP and methionine. Synthetic lethal genetic analysis has identified MAT2A as an anticancer target in tumor cells lacking expression of 5′-methylthioadenosine phosphorylase (MTAP). Approximately 15% of human cancers are MTAP−/−. The remainder can be rendered MTAP− through MTAP inhibitors. We used kinetic isotope effect (KIE), commitment factor (Cf), and binding isotope effect (BIE) measurements combined wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(40 citation statements)
references
References 39 publications
2
38
0
Order By: Relevance
“…C) indicates that the early step of reaction has taken place, but the S114A mutant fails to provide the nucleophilic attack of methionine's sulfur atom against C'5 atom of AMP‐PNP, thus unable to produce SAMe. These observations are consistent with the suggestion that C‐O bond breaking takes place prior to C‐S bond formation at the catalytic transition state of human wt MATα2 . Previously our high‐resolution structure of SAMe+ADO+MET+PPNP wt MATα2 (PDB: http://www.rcsb.org/pdb/search/structidSearch.do?structureId=5A1I) had revealed that the Ser114 is the sole residue in the gating loop that interacts with AMP‐PNP via a water molecule.…”
Section: Resultssupporting
confidence: 88%
“…C) indicates that the early step of reaction has taken place, but the S114A mutant fails to provide the nucleophilic attack of methionine's sulfur atom against C'5 atom of AMP‐PNP, thus unable to produce SAMe. These observations are consistent with the suggestion that C‐O bond breaking takes place prior to C‐S bond formation at the catalytic transition state of human wt MATα2 . Previously our high‐resolution structure of SAMe+ADO+MET+PPNP wt MATα2 (PDB: http://www.rcsb.org/pdb/search/structidSearch.do?structureId=5A1I) had revealed that the Ser114 is the sole residue in the gating loop that interacts with AMP‐PNP via a water molecule.…”
Section: Resultssupporting
confidence: 88%
“…A solvent accessible active site of MAT enables this enzyme to tolerate analogues of methionine and (seleno)methionine substrates bearing longer alkyl chains and functional handles on S/Se-centres producing a suite of analogues such as 7-9 ( Figure 2). [21,25,39,[47][48][49] The in situ synthesis of these cofactor analogues can then be used as substrates to transfer functional handles catalyzed by a variety of O- (14 a-d), C-(14 e) and N-(14 g) MTases (Figure 4a). [9,[20][21]25,[37][38][39] In addition, Seebeck et al expanded their two-enzyme SAM regeneration strategy (Figure 3B) [35] to stereoselectively prepare L-or D-β-alkylated αamino acids amino acids such as 14 f ( Figure 4B), [40] which are challenging to prepare by conventional chemical synthesis.…”
Section: Enhancing the Scope Of Biocatalytic Alkylation Using Modifiementioning
confidence: 99%
“…An atom-efficient alternative to the use of ATP as the adenosyl donor is to use 5'-chloro-5'-deoxyadenosine (ClDA) catalyzed by the chlorinase SalL (Salinispora tropica, Figure 4C). [50] Although the substrate scope of wildtype SalL is narrower than of MAT, [20][21]37,39,44,[47][48] SalL is capable of SAM analogue synthesis and is compatible with a range of small molecule (14 h,j,k) [23][24]27] and DNA (14 i) [22,24] MTases, thereby enhancing the flexibility of enzymatic alkylation routes available ( Figure 4A, B).…”
Section: Enhancing the Scope Of Biocatalytic Alkylation Using Modifiementioning
confidence: 99%
See 1 more Smart Citation
“…MATV1 was able to alter the activity of MAT2 without changing its catalytic transition state (Firestone & Schramm, 2017;Murray et al, 2014), and the catalytic site of MAT2 was also preserved in the presence of MAT (Murray et al, 2016), indicating that the increase in activity is modulated by allosteric regulation. The restoration of the activity of the MAT1 R264H mutant by the regulatory subunit MATV1 or the compound SCR0911 suggests a similar binding interface.…”
Section: The R264h Mutation Weakens the Dimer-dimer Interface In Matamentioning
confidence: 99%